The impact of individual differences on human information acquisition behavior to enhance gaze-based wheelchair control - Jipp, Meike; Bartolein, Christian; Badreddin, Essameddin (IEEE International Conference on Systems, Man and Cybernetics, 2008, 2008)
Especially for severely disabled people, a powered wheelchair is an important means to participate in societal life. To optimally support people in need without putting an additional burden on them, methods have been developed to enable controlling an electrically powered wheelchair on the basis of the user's natural gaze behavior. While existing approaches consider psychological/physiological research results, they do not take differences in the cognitive and motor abilities of the wheelchair users into consideration. However, according to the study at hand, which analyzed the gaze behavior of 10 wheelchair users when acting in an environment with a varying degree of familiarity, these individual differences are important when interpreting the gaze behavior for enhanced wheelchair control. Implications for a natural gaze-based assistance system for electrically powered wheelchairs are provided.
Gesehen am 14.06.2019